2007
DOI: 10.1063/1.2800167
|View full text |Cite
|
Sign up to set email alerts
|

The von Neumann entropy asymptotics in multidimensional fermionic systems

Abstract: We study the von Neumann entropy asymptotics of pure translation-invariant quasifree states of d-dimensional fermionic systems. It is shown that the entropic area law is violated by all these states: apart from the trivial cases, the entropy of a cubic subsystem with edge length L cannot grow slower than L d−1 ln L. As for the upper bound of the entropy asymptotics, the zero-entropy-density property of these pure states is the only limit: it is proven that arbitrary fast sub-L d entropy growth is achievable.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 30 publications
0
37
0
1
Order By: Relevance
“…with a known prefactor [22][23][24][25][26][27]. Except for d = 1 this entanglement entropy does not even have the same scaling form as the CFT result, hence no direct comparison is possible.…”
Section: Fermi Surfacementioning
confidence: 99%
“…with a known prefactor [22][23][24][25][26][27]. Except for d = 1 this entanglement entropy does not even have the same scaling form as the CFT result, hence no direct comparison is possible.…”
Section: Fermi Surfacementioning
confidence: 99%
“…We recommend [6] for a recent review of such area laws, with an emphasis on rigorous results for many-particle systems on the lattice Z d .It is somewhat surprising that an area law is not quite valid for the simple system of a free Fermi gas in R d or Z d . Indeed, various studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] have suggested that the EE of its ground state grows (at least as fast) as L d−1 ln L. Physically, this slight logarithmic enhancement is due to the effective long-range correlations of the particles by the Fermi-Dirac statistics, the algebraic statement of Pauli's exclusion principle. Mathematically, the resulting "sharp" Fermi surface modifies the asymptotic analysis as L → ∞ in such a way that the extra factor ln L emerges.The theorem.…”
mentioning
confidence: 99%
“…if t ∈ [0, 1] and by h α (t) (1) with α = 1 has appeared meanwhile in many publications [21][22][23][24][25][26][27] and with general α > 0 (and d ≥ 2) besides in [24] also in [28,30].…”
mentioning
confidence: 99%
“…[3]). For a system with short-ranged interactions in d spatial dimensions, the area law states that the entanglement entropy of a region A of linear size L grows like L d−1 , that is like the area |∂A| of the boundary ∂A of A. Fermi liquids are extremely interesting from an entanglement perspective because they possesses long-range entanglement that manifests as a violation of the area law [4][5][6][7][8][9][10][11][12]. Indeed, entanglement entropy in a Fermi liquid ground state scales like L d−1 ln (L) hence showing a logarithmic violation of the area law.…”
Section: Introductionmentioning
confidence: 99%